2014
DOI: 10.1016/j.ccr.2013.12.007
|View full text |Cite|
|
Sign up to set email alerts
|

CARM1 Methylates Chromatin Remodeling Factor BAF155 to Enhance Tumor Progression and Metastasis

Abstract: Summary Coactivator-associated arginine methyltransferase 1 (CARM1), a coactivator for various cancer-relevant transcription factors, is overexpressed in breast cancer. To elucidate the functions of CARM1 in tumorigenesis, we knocked out CARM1 from several breast cancer cell lines using Zinc-Finger Nuclease technology, which resulted in drastic phenotypic and biochemical changes. The CARM1 KO cell lines enabled identification of CARM1 substrates, notably the SWI/SNF core subunit BAF155. Methylation of BAF155 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
249
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(260 citation statements)
references
References 37 publications
11
249
0
Order By: Relevance
“…Several of these N-terminal residues are predicted to be sites of posttranslational modifications, including multiple arginines that represent potential targets of the arginine methyltransferase enzymes PRMT1, PRMT4, and PRMT5 (31,32). We, and others, have shown that myeloid differentiation is regulated by specific arginine methylation events, and PRMT4 modifies several proteins in the larger DPF2 interactome, including RUNX1 and the SWI/SNF subunit BAF155 (8,33). Thus, the recognition of histone modifications by the PHD domains of DPF2 potentially integrates multiple epigenetic inputs and likely enables the targeting of DPF2 to specific chromatin sites.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these N-terminal residues are predicted to be sites of posttranslational modifications, including multiple arginines that represent potential targets of the arginine methyltransferase enzymes PRMT1, PRMT4, and PRMT5 (31,32). We, and others, have shown that myeloid differentiation is regulated by specific arginine methylation events, and PRMT4 modifies several proteins in the larger DPF2 interactome, including RUNX1 and the SWI/SNF subunit BAF155 (8,33). Thus, the recognition of histone modifications by the PHD domains of DPF2 potentially integrates multiple epigenetic inputs and likely enables the targeting of DPF2 to specific chromatin sites.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, Halo-tag and Flag-tag CARM1 (WT and QM) were expressed in HEK293T cells with CARM1 knocked out by ZFN (HEK293T CARM1 −/− ) [28]. Immunoprecipitation was performed using Anti-FLAG Âź M2 Beads.…”
Section: O-glcnacylation Does Not Affect Cellular Localization Stabimentioning
confidence: 99%
“…CARM1-null human embryonic kidney (HEK293T), MCF7 (ERa positive breast cancer cell line) and MDA-MB-231 (triplenegative breast cancer cell line) cell lines were described in [28]. CARM1-null Cal51 cell lines were generated using the same method as described in [28].…”
Section: Generation Of Carm1 (Wt or Qm) Stably Expressing Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations